Fluid–structure interaction in a follow-up study of arterio-venous fistula maturation - Daniel Jodko; Tracie Barber (Scientific Reports)
Abstract Arteriovenous fistula (AVF) is the preferred vascular access for hemodialysed patients. AVF is created surgically using the patient’s artery and vein. Once the connection (anastomosis) is made, the maturation process begins. Studies have shown that most AVFs do not survive beyond one year. This study presents fluid–structure interaction (FSI) modelling of non-Newtonian blood flow through an end-to-side radio-cephalic AVF, investigated weekly during a 15-week follow-up period and 1.5 years postoperatively using ultrasound methods. The aim was to collect qualitative and quantitative data regarding changes in hemodynamics and alterations in the walls of AVF vasculature. Different material properties were assigned to the artery, suture zone (anastomosis), and vein, while the stiffening of the venous arm over time was also modelled. The proposed FSI methodology can be implemented in future follow-up studies involving groups of patients. The main findings revealed: a) counter-rotating vortices in the anastomosis cross-section affecting local pressure conditions; b) different temporal progression of vorticity, shear strain rate, and turbulent kinetic energy and similarity of the temporal progression of WSS obtained under the assumptions of the rigid-walled and FSI; c) a negligible low-WSS zone in the presented thrombosis-free AVF; d) migration of the zone of maximal temporal wall deformation over time.